Risk Control Analysis Embroidery Process Using Failure Mode and Effect Analysis and Fault Tree Analysis - Inggit Marodiyah; Rendy Hadi Saputra (International Journal on Orange Technologies, 2026)
The embroidery industry is highly competitive, requiring companies to produce high-quality products. However, the embroidery process still exhibits a relatively high level of risk. From July to December, total production reached 22,000 units, with 1,200 units being defective, or approximately 5.45%. This study aimed to determine the highest risk level in the embroidery process using the Failure Mode and Effect Analysis (FMEA) method, analyze the root causes using Fault Tree Analysis (FTA), and provide recommendations for improvement. The results revealed seven types of risks in the embroidery process. Based on the FMEA analysis, the first highest risk was the embroidery machine suddenly stopping (RPN 432), the second was thread breaking during operation (RPN 384), and the third was tangled or clumped embroidery during the installation process (RPN 252). The FTA analysis indicated that the main causes stemmed from machine factors and production process settings. Recommendations for improvement include re-inspecting the machine to prevent failures and re-inspecting before production